Multiple Non- Familial Trichoepitheliomas in a NineYear Child - Samriti Sood; Mudita Gupta; Reena Kumari Sharma; Manju Rao (Nepal Journal of Dermatology, Venereology & Leprology)
Trichoepitheliomas are rare benign tumours of poorly differentiated trichogenic origin. They present as translucent lesions most commonly on centrofacial regions. Solitary lesions are seen in sporadic cases while multiple lesions are inherited in autosomal dominant pattern. We present a 9 year old child with multiple trichoepitheliomas  at classical sites with  none of the other  family members involved.